Plan de negocios de la exportación de miel de abejas a Alemania (2019)
This project describes a business plan for the export of honey from Colombia to Germany based on the consumption and demand analysis of this European country. Germany is one of the biggest consumers of this product, therefore, it is also one of the most attractive markets worldwide. For this monograph development, commercial, technical and financial strategies were analyzed in order to know the apicultural sector in Colombia and Germany. In this way, it was identified that there is a potential market and it was possible to build a commercial plan around the honey demand in the German city of Bremen.